PEMODELAN DAN PENYELESAIAN PERMASALAHAN PENJADWALAN PILOT DENGAN METODE EKSAK DEKOMPOSISI - Ahmad Rusdiansyah; Yani Dhina Mirenani; Zya Labiba; Nurhadi Siswanto (Institute of Research and Community Outreach - Petra Christian University, 2007)
Crew scheduling is one of most important operational problems in airline industries. Crew scheduling Problem consists of two steps that is